Dynamic Analysis of Turret-Moored FPSO System in Freak Wave - 唐友刚 李焱 王宾 刘树晓 朱龙欢 (China ocean engineering, 2016)
Freak wave is the common wave which has significant wave height and irregular wave shape, and it is easy to damage offshore structure extremely. The FPSOs（Floating Production Storage and Offloading） suffer from the environment loads, including the freak wave. The freak waves were generated based on the improved phase modulation model, and the coupling model of FPSO-SPM（Single Point Mooring） was established by considering internal-turret FPSO and its mooring system. The dynamic response characteristics of both FPSO and SPM affected by the freak wave were analyzed in the time domain. According to the results, the freak waves generated by original phase modulation model mainly affect the 2nd-order wave loads. However, the freak waves which are generated by random frequencies phase modulation model affect both 1st-order and 2nd-order wave loads on FPSO. What is more, compared with the irregular waves, the dynamic responses of mooring system are larger in the freak waves, but its amplitude lags behind the peak of the freak wave.